2018
DOI: 10.20882/adicciones.1151
|View full text |Cite
|
Sign up to set email alerts
|

Evitación experiencial y uso abusivo del smartphone: un enfoque bayesiano

Abstract: El uso del teléfono móvil se ha convertido en una actividad cotidiana en nuestro entorno más cercano. Dicho uso, según investigaciones recientes, tiene tanto aspectos positivos como negativos. Aunque hay controversia en cuanto a la denominación del fenómeno, se aprecia cierta preocupación por las consecuencias negativas que tiene el uso excesivo del teléfono móvil. Este estudio analiza la relación que se establece entre el uso abusivo del teléfono móvil y la evitación experiencial. Se utilizó una muestra compu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 40 publications
(54 reference statements)
0
4
0
6
Order By: Relevance
“…A following study reported high scores in maladaptive Cognitive-emotion regulation (CER) strategies such as self-blame, blaming of others ruminating and catastrophizing thoughts (18). Experiential avoidance (i.e., attempts to avoid thoughts, feelings, memories and physical sensations) has been associated with excessive smartphone use and social networks (19). Childhood emotional maltreatment correlated with problematic smartphone use in adolescents, and it was mediated by body image difficulties, depression, and social anxiety (20).…”
Section: Insecure Attachment Poor Cognitive-emotional Regulation and Communication Problemsmentioning
confidence: 99%
“…A following study reported high scores in maladaptive Cognitive-emotion regulation (CER) strategies such as self-blame, blaming of others ruminating and catastrophizing thoughts (18). Experiential avoidance (i.e., attempts to avoid thoughts, feelings, memories and physical sensations) has been associated with excessive smartphone use and social networks (19). Childhood emotional maltreatment correlated with problematic smartphone use in adolescents, and it was mediated by body image difficulties, depression, and social anxiety (20).…”
Section: Insecure Attachment Poor Cognitive-emotional Regulation and Communication Problemsmentioning
confidence: 99%
“…These findings are consistent with the study conducted on a sample of 1176 participants (828 women) with ages ranging from 16 to 82 ( M = 30.97; SD = 12.05) using the SAS-SV and AAQ-II scales where the authors found that EA and social networks usage were found to be directly related to smartphone addiction. [ 18 ] Another study inferred that smartphone use was positively related to EA as it was used as a strategy to avoid discomfort. [ 19 ] DM was a significant predictor of PSU in the complete sample as well as based on gender.…”
Section: Discussionmentioning
confidence: 99%
“…Esto concuerda con lo visto en los estudios de Gil et al (2015), Marín Díaz et al (2018 y Moral Jiménez y Fernández Domínguez (2019). En esta línea, el estudio de Peña García et al (2018) postula que esa búsqueda de sensaciones positivas a través del teléfono móvil puede terminar desembocando en las adicciones comportamentales. Del mismo modo, cabe subrayar que 2 de cada 10 jóvenes pierden horas de sueño por preponderar el uso del dispositivo móvil a altas horas.…”
Section: Estudios De Investigaciónunclassified
“…Esto puede deberse al fenómenoFOMO (Cuesta Cambra et al, 2020), lo que fomenta el uso continuado y la ansiedad ante la falta de contacto por parte de los demás, que siembra la idea de una marginación ficticia. Por otro lado, la ansiedad puede venir provocada por la falta de sensaciones positivas que se obtienen al contactar con los demás a partir de las redes sociales, lo que no solo fomentaría este tipo de comportamientos, sino que los mantendría a lo largo del tiempo (Ruiz-RuanoGarcía et al, 2018). Cabe añadir que la ansiedad ante la falta de mensajes y llamadas es directamente proporcional a la frecuencia de uso del dispositivo(García del Castillo et al, 2019).En cuanto al sexo, no se encontraron diferencias estadísticamente significativas con respecto al uso problemático del móvil.…”
unclassified